The evolution of real disparities in Portugal among the NUTS III regions. An empirical analysis based on the convergence approach. - Elias Soukiazis; Micaela Antunes (European Regional Science Association (ERSA), 2004)
The aim of this paper is to explain regional convergence in Portugal, at Nuts III level, in terms of per capita income and productivity. In doing so, we employ an alternative estimation approach based on panel data analysis that allows for individual differences across regions, avoiding with this way the omitted variable bias occurred in single cross-section regressions. The known concepts of absolute and conditional convergence are tested between the 30 Portuguese regions, as well as, the importance of some conditioning structural factors related to resource allocation and demand conditions. Our evidence shows that convergence among the 30 regions in Portugal is rather conditional than absolute, both, in terms of per capita income and productivity. On the other hand, labour shares in the main economic sectors as measures of resource reallocation are important in explaining convergence in per capita income and productivity. Output growth, reflecting demand conditions and labour composition by sectors are shown to be relevant conditioning factors in explaining the convergence process in productivity and controlling for differences in regional structures. Our evidence shows a more significant shift of labour from the primary to the tertiary sector and when this element is introduced into the convergence equations, convergence is shown to be higher. Keywords: absolute and conditional convergence, per capita income, productivity, labour shares, panel regressions.
Keywords: 330; absolute and conditional convergence; per capita income; productivity; labour shares; panel regressions